El pirata - Scott, Walter, 1771-1832. (Madrid : Estudio Didactica)
A shipwrecked pirate causes turmoil on a remote Scottish island in the late 17th century.
Translation of: The pirate.
Keywords: Pirates -- Scotland -- Fiction; Airplane crash survival. -- Fiction; Shetland (Scotland) -- History -- Fiction; Scotland -- History -- 1689-1745 -- Fiction; Historical fiction; Novela historica